IMPACT OF PHYSICAL ACTIVITY ON THE ANATOMY AND PHYSIOLOGY OF THE BRAIN IN CONTEXT OF ITS POTENTIAL USE IN THERAPY AND DISEASE PREVENTION - Monika Dąbek; Monika Gajda-Bathelt; Julia Kulczycka; Paulina Sadkowska; Zuzanna Perlicka; Karolina Smolińska; Katarzyna Jania; Weronika Popow; Michał Ciołkosz; Tomasz Antczak (International Journal of Innovative Technologies in Social Science, 2025)
Introduction an purpose of the research. Physical activity and exercise stimulate our brain on several levels, including improving neuroplasticity, while promoting the formation of new synaptic connections and reshaping its anatomical structures, particularly the hippocampus. The aim of the review was to determine the current state of knowledge about the impact of physical activity and exercise on brain function and their potential therapeutic use in dementia, Alzheimer’s disease and depression. Material and methods. The search process included searching PubMed and Google Scholar by keyword. The selection of articles was based on the title and abstract. Results. Muscles, under the influence of movement, begin to produce myokines and other substances that affect the nervous system. Only some of them are able to cross the blood-brain barrier. They affect the formation of new synaptic connections and changing of the brain structure, in particular the hippocampus. A special place in muscle-brain communication is occupied by BDNF, which stimulates the process of neuroplasticity, tissue regeneration and cognitive functions, and its production is increased by the work of skeletal muscles. These changes impact the development of cognitive functions and counteract the pathomechanisms of some diseases, such as dementia or Alzheimer’s disease. The positive effect of physical exercise in the treatment of depression has also been proven. Conclusions. Processes occurring in the human body during physical exercise affect the structure and function of the brain. Some studies show promising results with incorporating exercise into the treatment of dementia, Alzheimer’s disease and depression.